Ontological modeling of the sound system based on the heritage of Akhmet Baitursynuly - Yergesh Б.Ж.; Bekmanova Г.Т.; Syzdykova Г.О.; Zhumagulova А.А. (Eurasian Journal of Applied Engineering and Technology (EJAET), 2023)
At present, the development of scientific and linguistic foundations and IT resources to expand the activities and use of the Kazakh language as a language of interethnic communication in digital format is an actual task. To solve this problem, within the framework of grant No. BR11765535, the “Akhmettanu” intellectual system is being developed, which includes a database on the scientific heritage of Akhmet Baitursynuly and new knowledge systems for all structural layers of the language in the light of his teachings. The article describes ontological models developed on the basis of the knowledge base of the structural levels of the Kazakh language on the example of the sound system, according to the teachings of Akhmet Baitursynuly. These models are the basis for the development of an intelligent system. Protégé editor was used for applied ontological modeling of the language sound system following the heritage of Ahmet Baitursynuly. The ontological model of the sound system in the work consists of classes (concepts), their properties and instances (individuals). New results of the scientific and linguistic foundations of the Kazakh language for various intelligent systems that process natural language have a direct impact on the development of information and communication technologies and the digitalization of the Kazakh language in Kazakhstan.